Dreamworld or dystopia? : the Nordic model and its influence in the 21st century / Michael A. Livingston. - Livingston, Michael A. (Cambridge University Press, 2022)
The Nordic Model was originally understood as a compromise between Western and Soviet systems. The Soviet Union has been gone for a generation, but the Nordic Model survives. Much of this has to do with the Model's change from an economic to a largely cultural model. In particular the Model has come to emphasize human (especially women's) rights; environmental consciousness; and cultural innovation. While these each contain an element of fantasy, they retain sufficient substance to provide encouragement to 'progressive' circles in the United States, United Kingdom, and other countries. Important in its own right, the Nordic Model provides a fascinating case study of the transmission of goods and ideas between different regions, and the ability of a small and out of the way region to maintain its own identity in a globalized world.